Application of the Problem Based Learning (PBL) Model to Students' Critical Thinking Ability in Class VI IPS Learning at SDN 51 Banda Aceh - Sahfitri,S, Dewi; Mislinawati, Mislinawati; Husin, M. (Elementary Education Research, 2023)
The aim of the research is to find out the application of the problem-based learning model to the critical thinking skills of grade VI SD 51 Banda Aceh students and what are the teacher's obstacles in applying the PBL model. This study used a qualitative approach with participatory observation data collection techniques and unstructured interviews. data analysis techniques through data collection, data reduction, data display, and verification. The results obtained by 4 out of 5 groups were at a very high level on the criteria for critical thinking ability, the remaining 1 group was at a high level on the criteria for students' critical thinking ability, besides that the application of the problem based learning (PBL) model to students' critical thinking skills in social studies learning was running smoothly. smoothly and optimally also the learning objectives are achieved. Therefore by applying the problem based learning (PBL) model in class VI it can improve students' critical thinking skills, especially in social studies learningKey words: Problem Based Learning Model, IPS